Video in Blendend Teacher Education: A Tool for Practicing Teaching Analysis - Stara, Jana; Krčmářová, Tereza; Krátká, Jana (Revija za elementarno izobraževanje, 2023)
The article presents a case study of using videos to develop primary school student teachers’ skills when analysing teaching. It is based on a content analysis of teaching observations, students’ written work, teacher feedback, curriculum, student evaluation, and teacher interviews. The research results show that using video is meaningful and motivating to student and university teachers. However, students rarely draw on theoretical knowledge in analysing the situations. To connect theory and practice, it is desirable to consistently apply the requirement to reflect on observed phenomena with the underpinning of theory and to strengthen the connections between theoretical and practical courses.
Keywords: teacher education, teacher training, video use, blended teacher education